2018
DOI: 10.1080/19420889.2018.1502586
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of quantitative trait loci related to primary rice root growth as a response to inoculation with Azospirillum sp. strain B510

Abstract: Azospirillum sp. strain B510 has been known as the plant growth-promoting endophyte; however, the growth-promotion effect is dependent on the plant genotype. Here, we aimed to identify quantitative trait loci (QTL) related to primary root length in rice at the seedling stage as a response to inoculation with B510. The primary root length of “Nipponbare” was significantly reduced by inoculation with B510, whereas that of “Kasalath” was not affected. Thus, we examined 98 backcrossed inbred lines and four chromos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Therefore, such statements could explain the negative performance of cultivar Syn 488 since the carotenoid content was reduced and POD and SOD activity remained very close to the control condition. Such data reinforce the idea that the genetic characteristics of the hybrids can influence inoculation in response to greater or lesser root exudation and the type of metabolite released (Pereira et al, 2020), combined with the genetic role of the hybrids in terms adhesion root to bacterial cells (Rojas et al, 2013;De león, Castellanos, Ling, Rojas-Hernández, & Roder, 2015), as well as the presence and transcriptional regulation of genes linked to molecular signaling and plant growth (Vargas et al, 2012;Masuda et al, 2018). Moreover, metabolic routes linked to plant defense must also change so that the infection/inoculation process is efficient without damaging the host plant (Thomas et al, 2019).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Therefore, such statements could explain the negative performance of cultivar Syn 488 since the carotenoid content was reduced and POD and SOD activity remained very close to the control condition. Such data reinforce the idea that the genetic characteristics of the hybrids can influence inoculation in response to greater or lesser root exudation and the type of metabolite released (Pereira et al, 2020), combined with the genetic role of the hybrids in terms adhesion root to bacterial cells (Rojas et al, 2013;De león, Castellanos, Ling, Rojas-Hernández, & Roder, 2015), as well as the presence and transcriptional regulation of genes linked to molecular signaling and plant growth (Vargas et al, 2012;Masuda et al, 2018). Moreover, metabolic routes linked to plant defense must also change so that the infection/inoculation process is efficient without damaging the host plant (Thomas et al, 2019).…”
Section: Discussionsupporting
confidence: 72%
“…Moreover, side effects, such as changes of the plant's defense system, are reported in the literature, presenting an increase in antioxidant enzymes and pigments (Alen'kina, Romanov, & Nikitina, 2018), with a response significantly linked to the modulation of the expression of genes related to plant growth and development (Masuda et al, 2018;Thomas et al, 2019). In this sense, Azospirillum brasilense can promote changes in seed germination even in a short period, with direct effects on the number of normal seedlings emerged and their germination speed due to the more significant synthesis of gibberellin, which possibly triggers greater enzyme activity linked to carbohydrate degradation and translocation to the embryo (Dartora, Marini, Guimarães, Pauletti, & Sander, 2013;De Morais, De Brito, Brandão, & Rezende, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The trait relative root growth showed significant association with five markers namely RM222, RM337, RM223 RM494 and RM16686 present on the chromosomes 10, 8, 8, 6, and 4, respectively. According to the earlier mapping study, the QTLs for root length were reported on chromosome 8 [ 17 ] and chromosome 6 [ 15 , 33 , 34 , 35 ] but at different locations. The QTLs detected in this investigation for regulating RRG were designated as qRRG10 .…”
Section: Discussionmentioning
confidence: 99%
“…Seeds were submerged in hot water at 55°C for 10 min to sterilize them as described in Masuda et al (2018). The sterilized seeds were placed in glass petri dishes with 0.2% Plant Preservative Mixture™ (PPM-100, Plant Cell Technology supplied by Nakarai Tesc Co., Kyoto, Japan) solution and incubated at 15°C for four days.…”
Section: Evaluation Of Coleoptile Elongation and Qtl Detectionmentioning
confidence: 99%